Temporal and spatial hydrogeochemical evolution and lead isotopic composition of a contaminated stream of Taxco, Guerrero, Mexico - Natasha Mylena Quevedo-Castañón; Oscar Talavera Mendoza; Sergio Adrián Salgado-Souto; Joaquin Ruiz; Azucena Dótor-Almazán; Alejandro Hermelindo Ramírez-Guzmán; Laura Sampedro-Rosas; José Luis Rosas-Acevedo; José Daniel Chávez-González (Revista Mexicana de Ciencias Geológicas)
Discharge of Acid Mine Drainage (AMD) produced within flooded mines is a major environmental issue in most polymetallic mining sites severely impacting nearby natural resources and producing a serious menace to the ecosystem and humans. The identification of both natural and anthropological factors influencing the bioavailability of toxic elements is relevant in revealing their behavior but also in the design of strategies for mitigating adverse effects to the environment. For these purposes, we carried out a spatial and seasonal hydrogeochemical (total and soluble contents) and a lead isotopic study of the AMD of the Xochula stream in the mining region of Taxco, Guerrero, in southern Mexico. The AMD is produced by the periodic discharge from the flooded Guerrero mine to the Xochula stream and is characterized by low to moderate pH, high sulfate, and high total and soluble metal contents. The AMD shows significant spatial but smaller temporal variations. Flow of AMD through a culvert made of concrete produces the most important chemical changes recorded regardless of the time of year significantly decreasing the electrical conductance and the concentration of total and soluble potentially toxic elements. Distribution of metals and As between dissolved and particulate-bound species is pH-controlled. Due to the short interaction time between the AMD and bedrock and the formation of coatings, lithology plays a minor role in neutralization, whereas mixing of AMD with freshwater is only significant in the less acidic segment of the stream. Neutralization of AMD entails a significant decrease of the concentration of both total and soluble metals and As and chemical speciation indicates that oxides, carbonates and sulfates are the reactive phases. The Pb isotopic composition reveals that metals derive from the Taxco ore deposit and that AMD is influenced by rocks of the Morelos and Taxco Schist formations.